Isoniazid induces oxidative stress, mitochondrial dysfunction and apoptosis in Hepg2 cells - Bhadauria, S.; Singh, G.; Sinha, N.; Srivastava, S. (Cellular and Molecular Biology, 2007)
Isoniazid (INH) continues to be a sheet anchor in treatment of tuberculosis, however its chronic administration is known to cause hepatotoxicity through a poorly defined mechanism. Ellucidation of mechanism underlying INH induced hepatotoxicity may be beneficial in devising ways to counteract toxic manifestations. In view of this concentration dependent effects INH were evaluated in hepatoma cell line (Hep-G2). INH exposure produced cytotoxic effects in Hep-G2 cells in a characteristic dose dependent manner. There was considerable cell detachment, loss of viability and alterations in cellular morphology that were indicative of toxic insult. We observed cell shrinkage at highest concentrations (88Î¼M) suggesting an involvement of apoptosis. This finding was substantiated by the flow cytometry data and DNA fragmentation analysis which clearly indicated that INH induced cytotoxicity, was being mediated by induction of apoptosis. Furthermore there was mitochondrial dysfunction as indicated by significant inhibition of MTT Reduction as compared to control at all the concentrations and depletion of cellular glutathione (GSH) content along with increased production of Reactive oxygen species (ROS). Collectively these findings led us to conclude that INH induced apoptosis in Hep-G2 cells is mediated by generation of oxidative stress.Isoniazid (INH) continues to be a sheet anchor in treatment of tuberculosis, however its chronic administration is known to cause hepatotoxicity through a poorly defined mechanism. Ellucidation of mechanism underlying INH induced hepatotoxicity may be beneficial in devising ways to counteract toxic manifestations. In view of this concentration dependent effects INH were evaluated in hepatoma cell line (Hep-G2). INH exposure produced cytotoxic effects in Hep-G2 cells in a characteristic dose dependent manner. There was considerable cell detachment, loss of viability and alterations in cellular morphology that were indicative of toxic insult. We observed cell shrinkage at highest concentrations (88Î¼M) suggesting an involvement of apoptosis. This finding was substantiated by the flow cytometry data and DNA fragmentation analysis which clearly indicated that INH induced cytotoxicity, was being mediated by induction of apoptosis. Furthermore there was mitochondrial dysfunction as indicated by significant inhibition of MTT Reduction as compared to control at all the concentrations and depletion of cellular glutathione (GSH) content along with increased production of Reactive oxygen species (ROS). Collectively these findings led us to conclude that INH induced apoptosis in Hep-G2 cells is mediated by generation of oxidative stress.